OP0006 A Large National Cohort of French Patients with Chronic Recurrent Multifocal Osteitis. (23rd January 2014) - Wipff, J.; Lemelle, I.; Pajot, C.; Duquesne, A.; Lorrot, M.; Faye, A.; Bader-Meunier, B.; Brochard, K.; Despert, V.; Grall-Lerosey, M.; Marot, Y.; Nouar, D.; et al.
Abstract : Background: Frequency of chronic recurrent multifocal osteomyelitis (CRMO), also known as nonbacterial osteomyelitis, seems to be underestimated and often leads to consequential residual impairments. Objectives: The aim of this study was to collect the French cases of CRMO in order to precise clinical, biological, radiological and histological features. Methods: In the absence of validated international diagnostic criteria, our inclusion criteria were: patient with at least one lesion of aseptic osteitis highlighted by imaging techniques (MRI or isotopic bone scan) and beginning before 18 years. Exclusion criteria were: onset after 18 years, other diagnosis (malignancy, infection, enthesitis related arthritis). Results: 164 patients were included (115 females and 49 males): mean aged was 16.7±4.6 years and mean age at diagnosis was 11.1±2.9 years. The mean time between first symptom and diagnosis was 18±25.5 months. 46/164 (28%) patients had initial unifocal lesion In multifocal forms (118/164, 72%), the mean number of clinical locations was 3.4±1.7. 32/164 patients had fever and 109/164 had inflammatory syndrome. 21/164 patients had associated lesions (4 inflammatory bowel disease and 18 cutaneous lesions) and 47/164 had a familial history of psoriasis, spondyloarthritis, inflammatory bowel disease. Radiographs and/or bone scan and/or MRI confirmed multifocal involvement in 21/46 cases with initial clinical unifocal symptom. On the remaining 25 unifocal cases, clinical exam and imaging during evolution allowed to confirm that 12/25 patients had multifocal CRMO form: only 13/165 (8%) patients had persisting unifocal form. Bone biopsies were performed in 109 cases. The use of Jansson score, when it was applicable (n=88) before diagnosis, would have avoided 11 bone biopsies. NSAIDs were given as first line therapy to 159/164 patients. DMARDs were used in 28 patients, bisphosphonates in 16 and anti-TNFα in 13. Persisting unifocal patients were similar to multifocal except for a lesser use of DMARDs / biological treatments (BT = bisphosphonates and/or anti-TNFalpha). Comparison between CRMO patients needing or not BT showed differences for the gender (male: 52% vs 26%, p=0.01), multifocal form (96% vs 82%, p=0.04) and presence of sequelae[cd1] (43% vs 19%, p=0.009). Only 65 patients (40%) were considered in remission at the last visit after a mean follow-up of 50.3±39.7 months. 37/161 patients had sequelae including localized deformations (n=19) or vertebral fractures (n=6). Conclusions: This cohort is the largest published CRMO cohort. Our results suggest that clinical evolution and repeated imaging technics (bone scan, MRI) could confirm the multifocal pattern of osteitis in initial unifocal form. Jansson score may also contribute to avoid 12% of bone biopsies. NSAIDs remained the main efficient first line treatment. Male gender and initial multifocal form are associated with the use of bisphosphonates and/or anti-TNFalpha. Disclosure of Interest: None Declared